2016
DOI: 10.1139/apnm-2015-0518
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stress, human performance, and physical employment standards

Abstract: Many physically demanding occupations in both developed and developing economies involve exposure to extreme thermal environments that can affect work capacity and ultimately health. Thermal extremes may be present in either an outdoor or an indoor work environment, and can be due to a combination of the natural or artificial ambient environment, the rate of metabolic heat generation from physical work, processes specific to the workplace (e.g., steel manufacturing), or through the requirement for protective c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(98 citation statements)
references
References 157 publications
3
84
0
Order By: Relevance
“…It was found that in the hot environment, the self selected workload was significantly reduced by 20% for the lifting task and that heart rate was significantly increased by 9 -10 beats. Stephen S Cheung et al 18 , have reviewed the effect of thermal stress, human performance and physical employment standards. The review surveys the major occupational impact of thermal extremes and existing employment standards, proposing guidelines for improvement and areas for future research.…”
Section: Impact Factor (Jcc): 76197 Scopus Indexed Journal Naas Ratimentioning
confidence: 99%
“…It was found that in the hot environment, the self selected workload was significantly reduced by 20% for the lifting task and that heart rate was significantly increased by 9 -10 beats. Stephen S Cheung et al 18 , have reviewed the effect of thermal stress, human performance and physical employment standards. The review surveys the major occupational impact of thermal extremes and existing employment standards, proposing guidelines for improvement and areas for future research.…”
Section: Impact Factor (Jcc): 76197 Scopus Indexed Journal Naas Ratimentioning
confidence: 99%
“…Thus, researchers must be aware of how best to quantify the physiological impact of diverse environments. One stress index was highlighted by Cheung et al (2016), with regard to heat exposure: the wet-bulb globe temperature (WBGT) index. The authors drew attention to its limitations, as summarized by Budd (2008).…”
Section: Thermal Considerationsmentioning
confidence: 99%
“…Notwithstanding those qualifications and its ubiquitous workplace use, additional reservations concerning that index are provided below, but with a particular emphasis upon heat exposure within physically demanding occupations. This knowledge is relevant not just to the collection of data during the characterization of working duties (Table 1), but also to recruit screening, for the environmental impact can often represent one of the more physiologically demanding aspects of the job (Cheung et al 2016;McLellan and Havenith 2016). With regard to the heat and coldtolerance testing of potential recruits, readers are directed to the next section of this communication.…”
Section: Thermal Considerationsmentioning
confidence: 99%
See 2 more Smart Citations